Engineering the NiO/CeO2 interface to enhance the catalytic performance for CO oxidation. Issue 119 (18th November 2015) - Zou, Weixin; Ge, Chengyan; Lu, Minyue; Wu, Shiguo; Wang, Yongzheng; Sun, Jingfang; Pu, Yu; Tang, Changjin; Gao, Fei; Dong, Lin
Abstract : In this work, NiO/CeO2 catalysts were synthesized with tunable CeO2 crystal facets ({110}, {111} and {100} facets) to study the crystal-plane effects on the catalytic properties. Abstract : In this work, NiO/CeO2 catalysts were synthesized with tunable CeO2 crystal facets ({110}, {111} and {100} facets) to study the crystal-plane effects on the catalytic properties. Kinetic studies of CO oxidation showed that NiO/CeO2 {110} had the lowest activation energy. Furthermore, the obtained samples were characterized by means of TEM, XRD, Raman, N2 -physisorption, UV-Vis DRS, XPS, H2 -TPR and in situ DRIFTS technologies. The results demonstrated that the geometric and electronic structures of the nickel species were dependent on the NiO/CeO2 interfaces, which had an influence on the synergetic interaction of absorbed CO and active oxygen species, and then the generation of the formate intermediate played an important role in the catalytic performance. The possible interface structures of nickel species on the CeO2 {110}, {111} and {100} surface were proposed through the incorporation model, suggesting that the advantageous NiO/CeO2 {110} interface facilitated CO adsorption/activation and active oxygen species formation, leading to the best catalytic performance.